Accompaniment of Houswives' Role in Increasing Family Income Through Utilizing Potato Harvest Remains in Dieng Village: Accompaniment of Housewives' Role in Increasing Family Income Through Utilizing Potato Harvest Remains in Dieng Village, Banjarnegara - Jinggo Aldino; Yeny Fitriyani; Ali Rochmat (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The role of housewives is very important in the family and society in general. A housewife is responsible for running the household and supporting the family's welfare. The assistance aims to help housewives, especially those who work as farm labourers in Dieng Village, utilize the remaining potato harvest into processed products with a higher selling value. Mentoring was provided to 10 homemakers working as agricultural labourers for 14 days, 14-30 September 2023. The problems were a need for more knowledge and skills in processing potatoes into processed products and challenges in marketing these products. In response to this problem, we designed a series of assistance on potato processing and marketing strategies via social media. The approach taken in this service activity uses Participatory Action Research (PAR). The PAR approach includes research by identifying problems that occur. Action assists in managing potato waste and marketing via Instagram. Participatory activities supported by homemakers can realize results and increase productivity and the family economy. Potatoes have many uses and can be processed into various foods. This assistance has shown positive results, and housewives have been able to innovate in processing leftover potatoes and marketing them through social media.